(untitled) (Research, Society and Development, 2021)
Anxiety is a biological signal that the body uses to protect against a threat. It is an emotion that is stimulated by the expectation of an event, real or not, that may threaten the conservation of the organism, where the demonstration of anxiety and stress is considered normal to the point of not causing suffering to the individual, as suffering can cause a pathological anxiety and later result in the so-called anxiety disorders, the objective of the research was to identify factors that predispose the occurrence of anxiety disorders in health professionals. is a bibliographic research of the integrative literature review type. As for the results, health professionals are susceptible to the appearance of anxiety disorders and other mental disorders, where the fact is due to the association of several risk factors such as: age, gender, marital status and the presence of chronic diseases and others. It is concluded that health professionals also need to receive physical and psychological assistance, in addition to social support and implementation of strategies aimed at minimizing the risk of developing mental disorders.